If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4x + 5) = 30 Reorder the terms: 6(5 + 4x) = 30 (5 * 6 + 4x * 6) = 30 (30 + 24x) = 30 Add '-30' to each side of the equation. 30 + -30 + 24x = 30 + -30 Combine like terms: 30 + -30 = 0 0 + 24x = 30 + -30 24x = 30 + -30 Combine like terms: 30 + -30 = 0 24x = 0 Solving 24x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '24'. x = 0 Simplifying x = 0
| 8m^2-12=-4 | | R-8.2+0.4r=-8.6 | | 3+30*2=x | | 4x^2+20x=3 | | 3+30*2=63 | | 2(84+14Y)-7y=-7 | | 1-12+2x=3x+2 | | 2r-4+3r=2.5 | | 3c-4c+1+5c+2+3= | | 4-2(2x-2)=2(4-3x) | | 9+5x=-40 | | 1-12x+2x=3x+2 | | 2r-4+3r=25 | | 4(a+7)-2a=a-3 | | 22x-8(2x-3)=50 | | 30+x=31 | | 5y-5=7+4(y-4) | | 8-5(a+2)=-6a+9 | | 15y+3+7x=180 | | 3x-18=-6x | | 4x-23=12x+53 | | 4x^2+72+324=0 | | 5p-(3p+p)=6p+1 | | 12x-2(4x+-4)=-24 | | ?8c+21=2c+1 | | 3x-4=8x+10 | | x+6(4)=18 | | 6x-2x-6=5 | | G^2-20g+10=0 | | -75-k=-92 | | 15x^4-30x^2+15x=0 | | -27+15x=33-15 |